Classifying Electronic Word of Mouth and Competitive Position in Online Game Industry - Bram Manuel; Dodie Tricahyono (Journal of Data Science and Its Applications, 2018)
The number of online review in online game industry growing significantly along with growing rateof internet adoption. With abundant number of data, one can acquire limitless insight, for example,information regarding of electronic word-of-mouth (e-WOM) whom greatly affecting consumerbehavior and business performance. Knowledge of e-WOM can be used as competitive intelligenceto deal with industrial competition. Therefore, this research answers how to classify e-WOM, whatare e-WOM aspects emerge in MMOFPS game, and how does comparison of e-WOM positivitybetween the three MMOFPS Game used as research objects. Dataset are constructed from Reviewpage of Steam website for respective games with total 499 reviews used as sample data. Then theanalysis conducted using Orange and Indico API as tools. Therefore, we found several noun wordsfrequently used as opinion target and we also found out that in aspect-level comparison, Game 2gain the highest e-WOM positivity value in community aspect and Game 1 gain the highest e-WOMpositivity value in general aspect. Thus, each respective game developer can manage to furtherdevelop their strategies from the information of their competitive position in the industry